Yield and quality of two sugar beet (Beta vulgaris L. ssp. vulgaris var. altissima Döll) cultivars are influenced by foliar application of salicylic acid, irrigation timing, and planting density - Khaled A.A. ABDELAAL; Sahar H. RASHED; Akbar HOSSAIN; Ayman EL Sabagh (Acta Agriculturae Slovenica)
Two field experiments were conducted to evaluate the time of foliar application of 100 ppm salicylic acid (SA), two irrigation (IR) timings, three levels of spacing (SP) hill-1 with different plant density on growth, yield and quality characters of two sugar beet cultivars (‘Samba’ and ‘Farida’). The results revealed that the foliar application of 100 ppm SA at 30 days after planting (DAP) and 14 days after the first application significantly influenced top fresh mass and root biomass of sugar beet plants. Conversely, the increasing period between planting and first irrigation scheduling led to significant differences in fresh mass, sugar yield, and sucrose % as well as purity % of sugar beet. Plants density with 60 × 20 cm spacing hill-1 was found to be better than the other two spacings for major characters, particularly root fresh mass, and Total soluble solids and purity %. Inversely, spacing at 60 × 15 cm, between hills gave the maximum levels of top fresh mass, root yield and sugar yield in the first season. The interaction effect between spacing hill-1 at 60 × 20 cm and 100 ppm SA applied at 30 DAP gave the maximum levels of increment for most of the studied characters, particularly for cultivar ‘Farida’.